Inklusi pada Kelompok Minoritas di Indonesia: Sebuah Refleksi Lapangan - Nurun Nisa' (Jurnal Identitas, 2023)
Indonesian society, with its level of diversity, in the name of ethnicity, religion and so on, has made the issue of identity one of the key issues in navigating this pluralistic country. Identity could be cementing or segregating the existing social groups. Within the tension of the two, in practice, those who are labeled as minority groups have experienced discriminatory treatment. Contestation over resources, for example, can lead to the creation of access barriers for minority groups. For this reason, the concept and practice of inclusion are relevant for Indonesia within which the issue of majorityminority has remained a problematic issue. Any exclusionary practices will create a potential conflict that can divide national unity. Lakpesdam’s experience in assisting 9 minority community groups shows that they experienced varying degrees of exclusion at the beginning of the assistance, including being excluded from social interactions, various unpleasant treatments, and stigma as a backward group, deviant, and other negative labels so that they were considered not equal to the other community groups.This has an impact on the limited access to resources. The results of the advocacy show that inclusion programs have been important factors in increasing community acceptance of the assisted group. This sequentially helps to issue various policies that are more inclusive and uphold the equality principle between citizens.